Analisis Kesesuaian Kode Diagnosis Utama Neoplasma Di Rumah Sakit Umum Daerah Dr. Soedirman Kebumen - Nurami, Amara Nabiila Sekar; Fauzi, Harry; Nur Indira, Zahrasita; Purnama Adi, Prisai (Akademi Perekam dan Informasi Kesehatan Imelda, 2024)
Neoplasm is a disease associated with abnormal tissue development due to neoplasia, which is the process of abnormal growth and development of body tissues that grow actively with the autonomic (uncontrolled) system. Information for a patient in a hospital will not be complete and useful if it has not been processed, then coding is required. Giving special diagnosis code of neoplasm should consider 3 things to get the right code, namely topography code, morphology, and behavior. However, in its implementation, there are still many errors in the coder's determination of the neoplasm diagnosis code. This has an impact on services to patients such as errors of Action, care and treatment. This study aims to determine the description of the accuracy of topography and morphology codes in neoplasm diagnosis at Dr. Sudirman Kebumen. The type of research used is descriptive quantitative. Based on the research obtained from 178 inpatient medical records in the case of neoplasms, the samples taken were as many as 39 C codes determined that the accuracy amounted to 8 (20.51%) inaccurate category amounted to 31 (79.49%). Inaccuracy in writing the neoplasm code due to the results of PA (anatomical pathology) that has not come out at the time of coding the disease, anatomical pathology Examination Result Sheet that often the results come late because the laboratory examination outside the hospital and the coding officer is less thorough, sometimes there is a doctor's writing that is less clear so that the difficulty of the officer in reading the diagnosis. This led to the inaccuracy of the neoplasm diagnosis code in Dr. Sudirman Kebumen in September 2020.